Two-Loop Correction to the Higgs Boson Mass in the MRSSM - Philip Diessner; Jan Kalinowski; Wojciech Kotlarski; Dominik Stöckinger (Advances in High Energy Physics)
We present the impact of two-loop corrections on the mass of the lightest Higgs boson in the minimal R-symmetric supersymmetric standard model (MRSSM). These shift the Higgs boson mass up by typically 5 GeV or more. The dominant corrections arise from strong interactions, and from the gluon and its N=2 superpartners, the sgluon and Dirac gluino, and these corrections further increase with large Dirac gluino mass. The two-loop contributions governed purely by Yukawa couplings and the MRSSM λ, Λ parameters are smaller. We also update our earlier analysis which showed that the MRSSM can accommodate the measured Higgs and W boson masses. Including the two-loop corrections increases the parameter space where the theory prediction agrees with the measurement.